Covid-19 syndemic in Africa as of 08/30/2023 - Mora-Alvarado, Darner (2024)
As would color the strategy titled “From writings to facts” established at the National Water Laboratory (Costa Rica), this study addresses the evolution of the Covid-19 pandemic-syndemic in Africa as of 08/30/2023, which completes the first study prepared in November 2021. The methodology involves the analysis of health indicators of confirmed cases of Covid-19, cases/100,000 inhabitants, deaths, deaths/million inhabitants, fatality and percentage advances in the vaccination against Covid-19. The results indicate that contrary to the initial forecasts of specialists, the expected health impact, Africa was the fourth most impacted continent behind America, Europe and Asia, surpassed only by Oceania. The countries with the most confirmed cases were South Africa, Morocco, Tunisia, Egypt and Libya. However, in cases/100,000 inhabitants, the first five places are occupied by Seychelles, Mauritius, Cape Verde, Botswana and Tunisia. Regarding mortality/million inhabitants, Sudan, Tunisia, Seychelles, Namibia and Swaziland are the most affected by health in Africa.